Pengembangan E-Komik Berbasis Heyzine Flipbook pada Materi Sistem Pencernaan bagi Peserta Didik Kelas VIII SMP - Rahayu Kismawati; Tias Ernawati; Puji Hariati Winingsih (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this research is to develop e-comics based on heyzine flipbook on digestive system material for students of class VIII junior high school. This research was developed using a 4D development model which includes the stages of define, design, develop, and disseminate. The data collection technique used in this study was observation, interviews, feasibility questionnaires, and student response questionnaires. Quantitative and qualitative descriptive were used to analyze the data obtained. The results of the study obtained that e-comics based on heyzine flipbook on the digestive system material for class VIII junior high school. The evaluation of the feasibility of e-comic by experts obtained 4.50 with very good criteria (SB). The product feasibility assessment by the science teacher got 4.68 with very good criteria (SB). The evaluation of the feasibility of e-comic by colleagues obtained 4.54 with very good criteria (SB). The results of student responses to the readability test of e-comic obtained an average value of 91% with very good criteria (SB). Based on these results, it can be concluded that the development of e-comics based on heyzine flipbook on digestive dystem material for class VIII junior high school students is suitable for use in science class VIII junior high school learning.